1996
DOI: 10.1148/radiology.198.3.8628855
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis: comparison of CT findings in HIV-seropositive and HIV-seronegative patients.

Abstract: HIV-seropositive patients had a lower prevalence of localized parenchymal disease and a higher prevalence of disseminated disease at CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2
9

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 0 publications
3
44
2
9
Order By: Relevance
“…Such findings were similar to those observed in the present study that also demonstrated agreement with studies developed by Leung et al (26) , which have demonstrated that HIVpositive patients present low prevalence of cavities and high prevalence of lymph node enlargement.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Such findings were similar to those observed in the present study that also demonstrated agreement with studies developed by Leung et al (26) , which have demonstrated that HIVpositive patients present low prevalence of cavities and high prevalence of lymph node enlargement.…”
Section: Discussionsupporting
confidence: 94%
“…The study developed by Leung et al (26) suggests that, in HIV-positive patients, atypical opacities with involvement of the middle and lower lobes may be secondary to the bronchogenic dissemination of the disease. According to these authors, atypical opacities were the most frequent finding in the HIV/tuberculosis association, with bronchogenic dissemination in 57% and miliary dissemination, in 17% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The patients included in the study were those that were referred to the specialist unit for management and were likely to have more complicated disease and therefore more obvious imaging findings. In patients who were HIV positive there was a lower prevalence of parenchymal consolidation, cavitation and post-primary pattern, and a higher prevalence of extrapulmonary and miliary disease than in those who were HIV negative [18,19], but this imaging pattern was not demonstrated in this study. Notably, the incidence of mycetoma was equally likely amongst HIV-positive and HIV-negative cases.…”
Section: Discussioncontrasting
confidence: 68%
“…As the CD4 cell count declines, the frequency of cavitation in pulmonary TB decreases. Data were pooled from 12 studies (6,19,34,66,71,105,143,144,159,199,208,210) that examined the frequency of lung cavitation associated with CD4 counts in patients coinfected with HIV and pulmonary TB. Patients whose CD4 count was above 200 cells/l had a 4-fold-higher odds of having cavitary pulmonary TB than those with CD4 counts below 200 cells/l (odds ratio, 4.44; 95% CI, 3.36, 5.88).…”
Section: Effect Of Hiv On Tuberculosis: Atypical Presentation and Extmentioning
confidence: 99%